Kaifa Kuntūr Qāma Bitashjī‘ Nahwa Aṭ-Ṭullāb Al-Judud Min Qabā’il Mukhtalifah Fī Indūnīsiyā Litaḥadduth Bil-‘Arabīyah Fī Ḥayātihim Al-Yawmīyah? How Gontor Encouraged New Students From Different Tribes In Indonesia To Speak Arabic In Their Daily Lives? - Yoke Suryadarma; Muhammad Wahyudi; Ahmad Gagah Gattuso; Muhammad Zaki; Arsyad Muhammad Ali Ridho (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
This research explores Gontor's initiative to encourage new students from various tribes in Indonesia to integrate Arabic into their daily communication. The problem addressed is the linguistic diversity in Indonesia, which often poses challenges in achieving proficiency in a foreign language like Arabic. This study aims to understand how Gontor's strategies effectively motivate these students to adopt Arabic in their everyday lives. Using a descriptive qualitative research method, data were collected through interviews, observations, and documentation to analyze the students' progress and experiences. The results indicate that Gontor's approach, including interactive language sessions, cultural immersion activities, and peer support systems, has significantly improved the students' Arabic language skills and confidence in using the language outside the classroom. The impact of this research is substantial, as it highlights the potential for similar programs to enhance language acquisition among diverse student populations. The conclusion is that Gontor's methods effectively promote Arabic language use in daily life, contributing to broader educational and cultural integration within Indonesia. This study provides valuable insights for educators and policymakers aiming to implement successful language learning programs in multilingual settings. Keywords: Arabic Environment, Gontor, Linguistic System, Language Activities.